Ultrasonic holography in ophthalmology — physical considerations* - CHIVERS, Robert C. (Archives of Acoustics, 1976)
The characteristics of the ultrasonic holography unit under clinical trial in ophthalmic applications is discussed with particular emphasis on its advantages and limitations. Discussion of the factors influencing the quality of pictures in B-scanning and holography is also given.